Pengaruh Penggunaan Teknologi Generatif AI terhadap Keandalan Audit Laporan Keuangan pada UMKM di Indonesia: Pengaruh - Sulistira, Putri; Ajeng Tieta Nawangsari (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study examines the impact of Generative Artificial Intelligence (AI) technology on the reliability of financial statement audits in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. With the advancement of digital technology, generative AI offers opportunities to improve accuracy, speed, and objectivity in the audit process. Through its ability to process large amounts of data, identify patterns, and detect anomalies in financial statements, this technology is expected to significantly support auditors in producing more reliable reports.This research methodology uses a quantitative approach by distributing questionnaires to external auditors, internal auditors, and financial consultants involved in MSME audits. The data obtained were analyzed using multiple linear regression techniques to examine the effect of the use of generative artificial intelligence (Generative AI) on audit reliability dimensions, namely accuracy, objectivity, and transparency. The results of the study are expected to demonstrate a significant contribution from the use of this technology in improving audit quality, while also providing practical implications for MSMEs and auditors to strengthen financial governance by utilizing artificial intelligence